PENGEMBANGAN STRATEGI PEMASARAN BAWANG GORENGPADA INDUSTRI âMUSTIKAâ KECAMATAN PALU BARAT DI KOTA PALU - Lestari, Murti Suci; Mappatoba, Marhawati; Lamusa, Arifuddin (AGROTEKBIS, 2018)
This study aims to identify internal and external environment factors, formulating of marketing strategies using SWOT analysis. The study was conducted in "Mustika" Industry in Sungai Lambangan Street, No. 15, West Palu district in the city of Palu in June - July 2016. Respondents were drawn in the study consisted of 5 persons namely 1 leader, 2 employees of the internal production,and 2 from the external consumer. The analysis was used the SWOT analysis.The results indicated the marketing strategy diagram SWOT of fried onions on "Mustika" industry is in quadrant I that is at the position of Strength- Opportunities (SO) strategy, it is utilizing of the marketing area with raw materials that are easily available so that it can maintain product quality and take advantage of government support, leveraging industry relationships with customers to improve certain customer with the long enough business experience so that with to take advantage of information and communication. Keywords: Fried onions, Mustika, SWOT Analysis.